SOSIALISASI DAN PENERAPAN TEKNOLOGI PEMELIHARAAN PARASITOID TELUR SEBAGAI AGEN HAYATI PENGENDALI HAMA PENGGEREK BATANG PADI - SUMIARTHA, KETUT; SUDIARTA, I PUTU (Buletin Udayana Mengabdi, 2012)
ABSTRACT This socialization and application conservation technology of egg parasitoid for biological control of the rice steam borer was conducted in order to give information for the farmer and application method of conservation technology egg parasitoid for biological control of the rice steam borer. It was conducted at August 14, 2006 at the subak building and agriculture area of Subak Lungatad, Banjar Jenah, East Peguyangan Village, West Denpasar District, Denpasar City, and Bali Province. Key Note Speakers come from Department of Plant Protection, Faculty of Agriculture, Udayana University (: Ir. I Ketut Sumiartha, MA.gr., I Putu Sudiarta, SP.MSi., Ir. I Wayan Susila, MS., Dr. G. N. Alit Susanta Wirya, SP., MA.gr., and Ir. I Gusti Ngurah Bagus, MP.), and also comes from Department of Agriculture Office Denpasar (I Wayan Swastika, SP., MSi.).The farmers like to follow the program and have understood about rice steam borer, egg parasitoids and applied method conservation technology of egg parasitoid. They hope those information can be accepted sustainable.